Micro-transfer patterning of dense nanoparticle layers: roles of rheology, adhesion and fracture in transfer dynamics. Issue 13 (12th March 2020) - Kusaka, Yasuyuki; Takei, Atsushi; Koutake, Masayoshi; Fukasawa, Tomonori; Ishigami, Toru; Fukuda, Nobuko
Abstract : Precise tuning of semidried states enables the high-resolution patterning of functional nanoparticle layers by fracture and adhesion. Abstract : Liquid inks deposited on substrates undergo spreading, coalescence, dewetting and subsequent drying kinetics, which limit the controllability of the cross-sectional shape and resolution of the printed patterns. By contrast, when the ink layers are previously semidried (highly-concentrated) and patterned on a polydimethylsiloxane sheet, single-micrometer features are resolved. Here we present the rheological, fracture and adhesive properties of semidried nanoparticle dispersion ink layers, which optimize the patterning of reverse offset printing with 5 μm spatial resolution. Under the appropriate patterning conditions, when the volume fraction ϕ of the particles in the semidried layers was approximately 46 v/v%, the layer elasticity was dominant in the linear viscoelastic region and a Burgers-type creeping property appeared. Under tensile strain, the semidried layers suddenly fractured at the sites of patterns with sharply defined sidewalls. In the semidried thin layers dominated by viscosity (lower ϕ ), the pattern edges were degraded owing to local transfer instability and possible subsequent spreading. Over-drying reduced the adhesiveness of the ink layers, implying an upper limit of ϕ for successful patterning. The characteristics of semidried inks contribute to establishing a versatile ink-formulation scheme of various functional nanomaterials for high-resolution printed applications.